Assessing student engagement and learners' behaviour in collaborative learning. (30th September 2021) - Lyngdoh, Andrea Nicola; Neelam, Netra; Sheorey, Pratima; Sinha, Manish
The purpose of this paper is to study the efficacy of analytics in enabling educators to understand learners' behaviour in a collaborative environment. A secondary research and review was carried out using the five-step approach of literature review. An empirical study to understand the learning efficacy in online mode was also carried out amongst students who had just moved to online mode of learning. The education space has seen a huge difference in what educators have been able to fulfil and the aspirations of the system at large. This has pushed educators and learners to seek solutions beyond the conventional spaces of learning, and thus, turn towards technology. Learning analytics as an evolving discipline has provided insights into a learner's journey as well as the barriers that may deter a learner's experience. This study intends to present an overview and gaps in understanding learners' behaviour and collaborative learning.